The Oceans - Mayer, Larry (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1993)
Abstract The oceans play a pivotal role in theearth system matrix and will thus be acritical component of future earth system research. This research will be driven by both technological advances and the need for an interdisciplinary approach. The scale (both spatial and temporal) of ocean-related problem soften requires expensive, large-scale, international programs. These programs are evolving into interdisciplinary looks at manageable sub-components of the system including: 1) investigations of global patterns of ocean and atmosphere circulation through networks of moorings, satellites and drifting sensors (e.g., World Ocean Circulation Experiment), 2) investigations of the role of the oceans in the global C02 system through deployment of sophisticated chemical and biological sensors, satellite observations, and flux measurements (e.g., Joint Global Ocean Flux Study), 3) establishment of a global database of high-resolution paleoclimatic time-series for investigations of the response of the earth/atmosphere system to known forcing functions and tochanges in boundary conditions (e.g.,Ocean Drilling Program (ODP) and Nansen Arctic Drilling paleo-oceanography), 4) investigations of mid-ocean ridge dynamics and the complex and linked processes of magmatism, hydrothermalcirculation, vent community development and lithosphère evolution (e.g.,RIDGE and ODP crustal drilling). Additionally, new developments in acoustic sensors and signal processing will greatly enhance our ability to imagethe oceans and the sea floor, and advances in data collection and data dissemination (networking) will significantly change the way we do globalscience. Arrays of autonomous sensors, satellite links, and global data networks may eventually reduce the cost of large-scale ocean-related research programs. Canada must be well-positioned both to contribute to, and to benefit from, these programs. Our challenge will be to ensure that the mechanisms (and funding levels) are available to support Canadian participation without compromising the efforts of the talented researcher who prefers to work independently, and to find the means to train excellent "earth system scientists" without compromising the high levels of specialized expertise needed to explore even small components of the system.